Reliability, accuracy and ecological validity of a wireless pressure sensor for swimming performance analysis - Coloretti, V.; Russo, G.; Bartolomei, S.; Fantozzi, S.; Cortesi, M. (Sports Engineering, 2025)
Pressure measurements are a valuable approach to evaluate swimming performance. However, the traditional cabled pressure devices could affect the swimming technique. In this study, the performances of a wireless and wearable pressure sensor were investigated in terms of i) reliability and accuracy, comparing hydrostatic and hydrodynamic pressures with the theoretical ones, ii) ecological validity, comparing performance when wearing or not sensors in free-swimming. Excellent test-retest, intra-, and inter-sensor reliability were observed for both hydrostatic and hydrodynamic pressures (ICC = 0.96) with low bias (MAE = 0.1 kPa, RMSE = 0.11 kPa) compared to theoretical ones. Free-swimming was affected by wearing or not the sensors with a significative reduction in terms of velocity (0.04 ms-1, p < 0.001) and stroke length (0.03 m, p < 0.05) but not stroke rate (p = 0.148). The wireless pressure sensor can measure the actual pressure in the aquatic environment with high accuracy and reliability, providing an ecological approach for monitoring hand pressure in swimming.